In vitro investigation of Mucuna pruriens seed extracts to treat erectile dysfunction - Natthachai Duangnin (2018)
© 2018, Chiang Mai University. M. pruriens seeds are a natural product with health benefits, including treating erectile dysfunction (ED). However, the active compounds and their mechanisms of action are unclear. In this study, we used polarity gradient extraction to isolate four fractions from the crude extract of M. pruriens seeds using hexane, EtOAc, BuOH, and water. All fractions were used to treat three cell lines: C6, Ea.hy926, and HCT-15. The water fraction significantly promoted nitric oxide (NO) production in C6 cells via neuronal nitric oxide synathase (nNOS) gene upregulation. M. pruriens fractions with high polarity promoted NO production in Ea.hy926 through the upregulation of endothelial NOS (eNOS) and inducible NOS (iNOS) genes. The BuOH and water fractions of M. pruriens extract were involved with cyclic GMP specific-phosphodiesterase (PDE5) and iNOS gene upregulation in HCT-15, which might result in maintenance of intracellular cGMP. According to the NIST library, 2,4-bis(1,1-dimethylethyl)-phenol, a phytochemical, may play a role in nNOS upregulation; this was only found in the water fraction. Protocatechuic acid, methyl ester, and γ-sitosterol were also found in the high-polar fractions of M. pruriens extract and might be involved with eNOS gene upregulation. The ability of M. pruriens extract to provoke NO production in neurons indicated the potential for using M. pruriens seeds as an alternative medicine for erectile dysfunction therapy.